Incidental non-traumatic right-sided diaphragmatic hernia during the attempt of laparoscopic cholecystectomy due to symptomatic gallstones – case report and literature review - Plevel, Danaja (Surgery and surgical endoscopy, 2023)
We present a case of a 76-year-old female patient who underwent an attempt at laparoscopic cholecystectomy due to symptomatic cholecystolithiasis. At laparoscopy, a right-sided diaphragmic hernia was discovered, and conversion to open surgery was performed. After the reduction of herniated liver and gallbladder, a cholecystectomy was performed. The diaphragmic hernia was repaired with direct sutures. An adult right-sided hernia is a rare condition. Most are treated in emergency settings when they become symptomatic. Treatment includes the reduction of herniated organs, their evaluation and repair, and closure of the diaphragm defect. No guidelines are available for the best treatment approach.
Keywords: diaphragmatic hernia; gallstones; laparoscopic cholecystectomy